1998
DOI: 10.1002/pro.5560070423
|View full text |Cite
|
Sign up to set email alerts
|

The dimerization motif of the glycophorin A transmembrane segment in membranes: Importance of glycine residues

Abstract: Abstract:The glycophorin A transmembrane segment homodimerizes to a right-handed pair of a-helices. Here, we identified the amino acid motif mediating this interaction within a natural membrane environment. Critical residues were grafted onto two different hydrophobic host sequences in a stepwise manner and self-assembly of the hybrid sequences was determined with the ToxR transcription activator system. Our results show that the motif LIxxGxxxGxxxT elicits a level of self-association equivalent to that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
191
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(203 citation statements)
references
References 21 publications
12
191
0
Order By: Relevance
“…In the heterodimerization model, we consider the three linked dimerization equilibria; homodimerizations of species A and B are defined by two homomeric dissociation constants (K a and K b , respectively), and the third equilibrium is defined by a heteromeric dissociation constant (K ab ) (eqs [6][7][8] By experimental design, the total concentration of the A species is always equal to that of the B species; this facilitates the analysis. Using eqs 10 and 11, which follow from this condition, and combining with eq 7, we obtain a secondorder polynomial expansion (eq 12).…”
Section: Methodsmentioning
confidence: 99%
“…In the heterodimerization model, we consider the three linked dimerization equilibria; homodimerizations of species A and B are defined by two homomeric dissociation constants (K a and K b , respectively), and the third equilibrium is defined by a heteromeric dissociation constant (K ab ) (eqs [6][7][8] By experimental design, the total concentration of the A species is always equal to that of the B species; this facilitates the analysis. Using eqs 10 and 11, which follow from this condition, and combining with eq 7, we obtain a secondorder polynomial expansion (eq 12).…”
Section: Methodsmentioning
confidence: 99%
“…Oligomerization-The GXXXG motif, in which two glycine residues are separated by any three amino acids on a helical framework, is recognized as a "dimerization motif," because it mediates the assembly of two transmembrane helices (35)(36)(37). Its presence within the TMD of VAP-B ( 235 GXXXG 239 ) prompted us to investigate its contribution to VAP-B oligomerization using mutagenesis studies and cross-linking experiments in intact cells.…”
Section: The Gxxxg Motif In the Tmd Is Insufficient To Drive Vap-bmentioning
confidence: 99%
“…In several studies, the minimal GpA dimerization motif has been identified, and dimerization is driven by a seven amino acid motif LIxxGVxxGVxxT [9]. While the two glycine residues in a distance of four (GxxxG-motif) appear to be of special importance for dimerization and dimer stability [8][9][10], all seven amino acids are directly involved in helix-helix interactions and align at the contact surface. However, interactions of the GpA TM helices are complex and not only modulated by the sequence context but also by the lipid and/or detergent environment [2,11,12].…”
Section: Introductionmentioning
confidence: 99%